Chromosome-level genome assemblies of the malaria vectors Anopheles coluzzii and Anopheles arabiensis. Issue 3 (15th March 2021) - Zamyatin, Anton; Avdeyev, Pavel; Liang, Jiangtao; Sharma, Atashi; Chen, Chujia; Lukyanchikova, Varvara; Alexeev, Nikita; Tu, Zhijian; Alekseyev, Max A; Sharakhov, Igor V
Abstract: Background: Anopheles coluzzii and Anopheles arabiensis belong to the Anopheles gambiae complex and are among the major malaria vectors in sub-Saharan Africa. However, chromosome-level reference genome assemblies are still lacking for these medically important mosquito species. Findings: In this study, we produced de novo chromosome-level genome assemblies for A. coluzzii and A. arabiensis using the long-read Oxford Nanopore sequencing technology and the Hi-C scaffolding approach. We obtained 273.4 and 256.8 Mb of the total assemblies for A. coluzzii and A. arabiensis, respectively. Each assembly consists of 3 chromosome-scale scaffolds (X, 2, 3), complete mitochondrion, and unordered contigs identified as autosomal pericentromeric DNA, X pericentromeric DNA, and Y sequences. Comparison of these assemblies with the existing assemblies for these species demonstrated that we obtained improved reference-quality genomes. The new assemblies allowed us to identify genomic coordinates for the breakpoint regions of fixed and polymorphic chromosomal inversions in A. coluzzii and A. arabiensis . Conclusion: The new chromosome-level assemblies will facilitate functional and population genomic studies in A. coluzzii and A. arabiensis . The presented assembly pipeline will accelerate progress toward creating high-quality genome references for other disease vectors.